PERILAKU INVESTOR ATAS INFORMASI NEGATIF DALAM SUATU INDUSTRI - Heriyanto .; Johan Gunady Ony; Suramaya Suci Kewal (Universitas Mercu Buana, 2019)
This study aims to examine empirically the investment behavior of investors over the announcement of financial distress of companies listed on the Indonesia Stock Exchange. The testing period in this study was 2005-2016. The behavior of investors in competing companies (non-delist) in the industry (known as intra-industry information transfer) can be seen from abnormal return patterns that occur in competitors' shares around the delist announcement day. Contagion effect occurs in competing companies in one industry that get negative reactions from investors while competitive effects occur in competing companies that get a positive reaction from investors over the delist announcement of other company. This study uses leverage and market capitalization of competing companies to explain the contagion and competitive effects. Sampling in this study uses a purposive sampling approach. Data analysis techniques in this study use one sample t-test. The number of samples in this study were 22 delist companies and 132 non-delist companies. This study showed that there was an intra-industry information transfer. Competitive effect occurs at t-3 and t+2 arround the delist announcement day. Specifically, market capitalization and leverage of non-delist can not explain the direction of intra-industry information transfer